Knowledge and Rhetoric in Medical Commentary : a Ancient Mesopotamian Commentaries on a Handbook of Medical Diagnosis (Sa-gig) - Wee, John (Cuneiform Monographs, 2019)
Knowledge and Rhetoric in Medical Commentary is intended for historians of medicine and interpretation, and explores the dynamic between scholastic rhetoric and medical knowledge in ancient commentaries on a Mesopotamian Diagnostic Handbook. In line with commentators' self-fashioning as experts of diverse disciplines, commentaries display intertextuality involving a variety of lexical, astronomical, religious, magic, and literary compositions, while employing patterns of argumentation that resist categorization within any single branch of knowledge. Commentators' choices of topics and comments, however, sought to harmonize atypical language and ideas in the Handbook with conventional ways of perceiving and describing the sick body in therapeutic recipes. Scholastic rhetoric-supposedly unfettered to any discipline-served in fact as a pretext for affirming current forms of medical knowledge.